Basic helix-loop-helix transcription factors, BHLHB2 and BHLHB3; their gene expressions are regulated by multiple extracellular stimuli - Kazuya Yamada (2005)
The E box sequence (5'-CANNTG-3') is found in the transcriptional regulatory region of a number of genes. Of the basic helix-loop-helix (bHLH) proteins binding to the E box sequence, class B of bHLH proteins, BHLHB2 (also referred to as the DEC1/Eip1/SHARP-2/Stra13/Clast5) and BHLHB3 (also referred to as the DEC2/SHARP-1/SHARP1), are transcription factors that contain a unique orange domain. These transcription factors repress the transcription of target genes not only via binding to the E box sequence but also via protein-protein interactions with other transcription factors. Both the BHLHB2 and BHLHB3 genes are widely expressed in both embryonic and adult tissues. Their gene expressions are regulated in a cell type-specific manner by various extracellular stimuli, such as growth factors, serum starvation, hypoxia, hormones, nutrient, cytokines, light, and infection. Therefore, these transcription factors play pivotal roles in multiple signaling pathways that impact many biological processes including development, cell differentiation, cell growth, cell death, oncogenesis, immune systems, circadian rhythm, and homeostasis. The structural features, functions, and biological roles of the novel bHLH transcription factors, BHLHB2 and BHLHB3, are discussed along with the mechanisms in which the genes encoding these factors are regulated.